Refleksi Penafsiran Ayat-ayat Dakwah Thomas McElwain - Muhamad (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
The purpose or target of da'wah (mad'u) is almost always fragmented, both among Muslims and non-Muslims. This article seeks to explore the opinions of Thomas McElwain, an expert on Hebrew and Semitic Studies, on da'wah verses in the context of the book's people. The method employed is concept analysis via content analysis with a textual approach. The study findings indicate that the idea of the root of da'wa is a manifestation of varied editorial perceptions of al-Quran verses and the diversity of synonyms for the term